(untitled) (Research, Society and Development, 2022)
Objective: To analyze evidence of care aimed at preventing and treating osteonecrosis of the jaws related to medication use. Method: Integrative review with search and selection in the following electronic databases: MEDLINE via Pubmed, LILACS and IBECS via VHL. Descriptors were extracted from controlled vocabularies and combined with OR and AND operators. The following were considered for inclusion: primary studies, published in Portuguese, English or Spanish and in the period from 2010 to 2021. The sample totaled 10 studies and the analysis was carried out in a descriptive way. Results: Osteonecrosis in the jaws induced by the use of medications is a rare, serious adverse event and a growing target of new studies that show the need for measures to prevent, control pain and promote quality of life. The preventive strategies were varied and involved the dental evaluation before the beginning of the treatment, the identification and classification of the risk, the use of radiography, daily supplementation of vitamin D, the topical application of fluoride, the use of mouthwashes based on chlorhexidine and the application of techniques for closing existing lesions. Among the therapeutic interventions, standard clinical care and conservative management stood out, as well as treatment with hyperbaric oxygen, subcutaneous teriparatide and the use of plasma rich in growth factors. Conclusion: Further investigations are needed to highlight the main dental strategies aimed at managing osteonecrosis related to medication use. Also, to demonstrate the dimension of the problem and promote valid, effective and evidence-based public policies.